2014
DOI: 10.1097/pcc.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Oxygen Saturation Correlate With S100B in Infants Undergoing Cardiac Surgery With Cardiopulmonary Bypass

Abstract: A wide cerebral arteriovenous difference measured by near-infrared spectroscopy during cardiopulmonary bypass is associated with increased serum S100B in the perioperative period and may be a modifiable risk factor for neurological injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In addition, an increasing number of studies focused on the role of S100β in cognitive function. In previous large-scale investigations, researchers regarded the S100β protein as the marker to evaluate the neurocognitive outcome following cardiac surgery (55,62,63). It is likely that these target genes are important in sevoflurane-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increasing number of studies focused on the role of S100β in cognitive function. In previous large-scale investigations, researchers regarded the S100β protein as the marker to evaluate the neurocognitive outcome following cardiac surgery (55,62,63). It is likely that these target genes are important in sevoflurane-induced neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,[27][28][29] In contrast to previous studies, we defined elevated S100B concentrations to evaluate the impact of cerebral oxygenation and other variables related to surgical treatment and perioperative management on S100B release. 22,23,[27][28][29] In contrast to previous studies, we defined elevated S100B concentrations to evaluate the impact of cerebral oxygenation and other variables related to surgical treatment and perioperative management on S100B release.…”
Section: Discussionmentioning
confidence: 99%
“…Although the kinetics of these molecules in serum remain largely unknown, these data support the hypothesis that the BBB remains permeable in the initial h following CPB but begins to close within the first postoperative day. Abu-Sultaneh et al (48) demonstrated a significant correlation between peak serum S100B following CPB with cerebral oxygen desaturation during surgery, as measured by near-infrared spectroscopy. Furthermore, it has been demonstrated that cerebral oxygen saturation is correlated with neurodevelopmental outcomes and brain MRI at one year of age (58).…”
Section: Discussionmentioning
confidence: 99%
“…The highly phosphorylated form of NF (pNF-H) is resistant to proteolysis and when released from damaged axons remains largely intact; thus, its presence in the blood is indicative of neuronal damage (44,45). Other biomarkers measured included a brain-specific isoform of enolase known as neuron specific enolase (NSE) (46) and S100, a 20 kDa protein belonging to the S100/calmodulin/troponin C superfamily of calcium-binding proteins that forms heterodimers (S100A1B) and homodimers (S100BB) in CNS glial cells and peripheral Schwann cells (47,48). …”
Section: Introductionmentioning
confidence: 99%